Impact of the COVID-19 pandemic on hospital admission rates for arterial hypertension and coronary heart disease: a German database study - Sasko, Benjamin; Matiakis, Marios; Seibert, Felix S.; Pagonas, Nikolaos; Hippe, Hans-Jörg; Babel, Nina; Ukena, Christian; Westhoff, Timm H. (Frontiers in Cardiovascular Medicine, 2024)
Background Endothelial damage is a crucial prerequisite for the development of atherosclerosis and contributes to hypertension. Since COVID-19 is associated with endothelial dysfunction and cardiovascular complications, it remains unclear if a persisting endothelial dysfunction is leading to an increased cardiovascular morbidity and mortality after the end of the pandemic. Methods Systematic multicentric retrospective analysis of 57.795 hospital admissions in Germany during two different time periods (post-pandemic era versus pre-pandemic era). Information on hospital admissions for hypertension, chronic coronary syndrome, unstable angina pectoris and acute myocardial infarction were extracted from the hospitals data systems. Additionally, six comorbidities and performed coronary interventions were monitored. Results Compared to the pre-pandemic era, there was no increase in hospitalizations for hypertension or myocardial infarction, but the total number of patient admissions with chest pain as the presenting symptom. At the same time, the number of performed coronary angiographies increased, but less patients underwent percutaneous interventions. Patients admitted with chest pain in the post-pandemic era were in general healthier with less comorbidities. Conclusion The present multicenter study found no evidence that a persisting endothelial dysfunction is leading to an increase in hospitalizations for hypertension or coronary artery disease after the end of the pandemic.